Zoology - Donald, Diana (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This is a collection of primary sources throwing light on the various aspects of interplay between zoology and visual culture in nineteenth-century Britain"--
Keywords: Zoology -- Great Britain -- History -- 19th century; Art -- Great Britain -- History -- 19th century; Art and society -- Great Britain -- History -- 19th century; SCIENCE / History; SCIENCE / Life Sciences / Zoology / General